MANAGEMENT DISASTER IN MATERNITY AREAS - Ai Rahmawati; Bhekti Imansari; Devita Madiuw; Ida Nurhidayah; Pipih Napisah; Yanti Hermayanti (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Indonesia is one of the countries in the world that is often affected by natural disasters. The disaster has broad-impact such as infrastructure damage, loss of material, and impacts on residents who live in the disaster area including pregnant women, postpartum women, and newborns. The impact that often occurs is stress in pregnant women and postpartum. Also, babies born also may have low birth weight and premature. The purpose of this literature study was to review disaster management in the maternity area in various countries. The electronic database included EBSCO hosts, PubMed and google scholar. Keyword for searching articles was